THE EFFECT OF FINANCIAL VARIABLE, NON FINANCIAL AND ECONOMIC MACRO TOWARD UNDERPRICING ON IPO IN BEI - Sulistyawati, Putu Iin; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Underpricing is an initial return which is obtained by investors when the stock price (IPO price) is lower than the prime market share price at the closing day (close price) in secondary market. This study aims to obtain the empirical evidence of the influence of financial leverage, auditor reputation and inflation towards underpricing on the initial public offering in BEI. Non-probality sampling method with purposive sampling technique are used in this study. Data collection method that used is a non-participant observation conducted in the Indonesian Stock Exchange (BEI). The data analysis that used is multiple linear regression analysis. The result of the analysis finds that the financial leverage have positive effect on the IPO underpricing and the auditor's reputation have negative affect on IPO underpricing.
Keywords: financial leverage, auditor reputation, inflation, and the initial public offering.